Reactions of perennial grain accessions to four major cereal pathogens of the Great Plains - Cox, C. M.; Cox, T. S.; Bockus, William W.; Peters, T.; Garrett, Karen A. (My University, 2007)
Methods of disease management used in annual grain crops, especially cultural practices designed to disrupt the disease cycle of a particular pathogen, will not necessarily be applicable to perennial grain crops. Resistance to multiple pathogens, therefore, will clearly be important in disease management. The objective of this research was to evaluate disease resistance in 10 perennial grain accessions (one to two accessions of each: perennial wheat (Thinopyrum sp. × Triticum aestivum), intermediate wheatgrass (Thinopyrum intermedium), perennial rye (Secale montanum), hexaploid triticale (Triticum turgidum × S. montanum), octoploid triticale (Triticum aestivum × S. montanum), tetraploid perennial rye (Secale cereale × S. montanum), and tall wheatgrass (Thinopyrum ponticum)) to tan spot (caused by Pyrenophora tritici-repentis), take-all (caused by Gaeumannomyces graminis var. tritici), wheat streak mosaic, and barley yellow dwarf, four important diseases of the Great Plains. Several of the grasses were resistant to tan spot, barley yellow dwarf, and wheat streak mosaic. Indeed, the wild grasses and perennial donors T. intermedium (including BFPMC1), T. ponticum, and S. montanum, in addition to Permontra, a tetraploid perennial rye, were highly resistant to all three diseases. Additionally, the remaining grasses tested were also more resistant to tan spot than the susceptible wheat control. However, none of the 10 grass accessions appeared highly resistant to take-all, and substantial losses in biomass were observed, although such effects may be moderated under field conditions due to the potential for take-all decline in perennial plantings.
Citation: Cox, C., . . . Peters, T. (2005). Reactions of Perennial Grain Accessions to Four Major Cereal Pathogens of the Great Plains. Plant Disease, 89(11) 1235-1240. https://doi.org/10.1094/PD-89-1235
Keywords: Perennial grain accessions; Cereal pathogens; Tan spot; Take-all; Wheat streak mosaic; Barley yellow dwarf; Great Plains